Kritik Levinas terhadap Kebijakan Luar Negeri Realisme : Konsep Etika dan Tanggung Jawab terhadap “Liyan”: Levinas's Critique of Realist Foreign Policy: The Concept of Ethics and Responsibility to the “Liyan” - Merici, Angela (Undiksha, 2025)
This article aims to analyze the realist foreign policy in the international relation field from the perspective of ethics of the responsibility for “the Others” by Emmanuel Levinas. The methodology used is the qualitative method with the literature studies by collecting and analyzing the cases from the journal and media reports. The findings in this analysis is that realist foreign policy is in really opposite way to the concept of responsibility towards the